Examination of the Influence of Betawi Language Elements on the Speech Morphology of Jakarta's Teenagers - Iskandarsyah Siregar; Arju Susanto (Britain International for Academic Research (BIAR-Publisher), 2023)
This research aims to explore how the Betawi language impacts the speech patterns of adolescents in Jakarta. Utilizing qualitative approach and descriptive analytics, the study focuses on words within sentences that show Betawi interference, categorized into affixation, reduplication, composition, and acronyms. Key findings reveal significant Betawi influence in the areas of affixation and reduplication. For instance, words were often modified with Betawi-inspired prefixes, suffixes, or confixes, and a specific form of repetition, 'dwilingga,' was also evident. Interestingly, no Betawi interference was found in composition and acronyms. This suggests Betawi language has a selective influence on speech morphology, primarily affecting affixation and reduplication. The study provides valuable insights for future research on linguistic influences in multi-ethnic and multi-lingual settings like Jakarta